The role of job satisfaction as the mediator between human resource practices and employees’ performance based on the assumption of Adams’ equity at Saudi ports Authority especially in cargo section - Saud Mira, Mohammed; Voon Choon, Yap; Kok Thim, Chan (International Journal of Psychosocial Rehabilitation, 2020)
The ports of Saudi Arabia are considered the most officious seaports in the Middle East. It has the leading and most expanded industry in the Middle East and plays a great, significant role in increasing the economics of the country. Saudi Ports Authority has nine main ports on the two coasts of the kingdom, which achieved 95% of trading goods through the kingdom’s seaports, and export share is 55%. However, cargo’s overstock is the major problem that just came up, which raises the expense of cargo’s handle to 200%. As a result, it reduces job opportunities and satisfaction in the employees of the cargo sector. Additionally, there is a lack of appropriate human resource practices. Therefore, our study takes a step to observe the effects of human resource exercise on worker’s performance and also the facilitating role of job satisfaction in the association between human resource practices and employee’s performance in Saudi Port Authority. Moreover, this study will validate the assumption of Maslow theory. A questionnaire-based survey was utilized in this study